“RELIGIOUS TOLERANCE IN BULGARIA TODAY” (Религиски дијалог и соработка, 2023)
Religious tolerance continues to grow today, but at a moderate pace. Even afterthe International Conference of Religious Tolerance in the Light of Human Rights in 1995in the capital of Bulgaria – Sofia the question of studying religious tolerance between differentreligious communities arose. New times open a wider horizon of worldview andnew generations become more responsive and tolerant of new personalities and religionmovements. In the increasingly global world in which we live, we are confronted every daywith different attitudes in the relations between different religious communities, their traditionsand customs. Unfortunately, there is both religious tolerance and religious intolerance.This study aims to show religious tolerance now and how different religious groupslive together side by side. Many new religious movements have emerged in the last fewyears. These religious movements are more or less accepted by different generations society.The sooner we seek answers to important questions such as peace and harmony betweendifferent religious communities and its implementation the sooner other answerswill emerge. We are all different as individuals, different in religion and understanding oflife. This is a root of the secret of our earthly path in the application of sharing, tolerance,respect of each other. However, there is still an imposition in human relationship. Quantitativemethod was used. Secondary data analysis is performed. Religious tolerance willalways be a leading topic for reflections between the struggle between good and evil, thedifference between white and black or the meaning of the eastern symbol “yin and yang”.Above all leading should be what kind of person you define yourself and what is your attitudeto the color world around you.